Glutamate in Male and Female Sexual Behavior: Receptors, Transporters, and Steroid Independence - Chiang, Vic Shao-Chih; Park, Jin Ho (Frontiers in Behavioral Neuroscience, 2020)
The survival of animal species predicates on the success of sexual reproduction. Neurotransmitters play an integral role in the expression of these sexual behaviors in the brain. Here, we review the role of glutamate in sexual behavior in rodents and non-rodent species for both males and females. These encompass the release of glutamate and correlations with glutamate receptor expression during sexual behavior. We then present the effects of glutamate on sexual behavior, as well as the effects of antagonists and agonists on different glutamate transporters and receptors. Following that, we discuss the potential role of glutamate on steroid-independent sexual behavior. Finally, we demonstrate the interaction of glutamate with other neurotransmitters to impact sexual behavior. These sexual behavior studies are crucial in the development of novel treatments of sexual dysfunction and in furthering our understanding of the complexity of sexual diversity. In the past decade, we have witnessed the burgeoning of novel techniques to study and manipulate neuron activity, to decode molecular events at the single-cell level, and to analyze behavioral data. They pose exciting avenues to gain further insight into future sexual behavior research. Taken together, this work conveys the essential role of glutamate in sexual behavior.